PERCENTAGE OF LACTOSE CRYSTALLIZATION IN WHEY CONCENTRATE BY LAB-SCALE CRYSTALLIZER - Pereira, João Pablo Fortes (2013)
It is noticeable the export growth of dairy products in Brazil in recent years, where concentrated and dehydrated products have great importance in sales volume, although the importation of some of these, as whey powder, still occurs in large quantities. Due to lack of data, process parameters and speci? c literature on technology, composition and durability, there is dif? culty in quality increase and application of technical regulations. In the present study was to avaluate the crystallization of lactose in three samples of whey concentrated to 50% w/w milk solids from the dilution of whey powder . After dilution, the whey concentrate was crystallized at a temperature of 25 °C in adapted lab-scale crystallizer. It was added 0.1% w/w of whey powder, which had the hole of crystallization nuclei. The measure of soluble solids in the mixture were realized by reading the samples every 20 minutes using an refractometer so that the curve was obtained. Microscopic analysis were conducted after the dissolution of the whey powder in order to verify the presence or absence of lactose crystals in the solution after its preparation. To determine the percentage of crystallization, it was used the formula suggested by Westergaard (1994). After the dissolution of whey powder, lactose crystals was observed under the microscope what indicates that the crystallization process began spontaneously. At the beginning of the experiment (0-180 minutes), there was an accelerated decrease in the amount of soluble solids and in the rate of crystallization. After this period, it occurred a slowly decrease in the soluble solids content and in the crystallization rate.